Analysis of the Role of Baznas and Zakat Collection Institutions in Supporting Sharia Green Banking in Indonesia - Amanda Angelina Hutomo; Elsisca Maharani Chintya Bella; Liya Marsya Ayu Nirmala Saputri; Safia Putri Vigianta; Amalia Nuril Hidayati (Takaza Innovatix Labs Ltd., 2025)
This research was conducted to gain an in-depth understanding of the contribution of the National Zakat Agency (BAZNAS) and Zakat Institutions (LAZ) in supporting the implementation of green sharia banking in the framework of sustainable development. Using a library research approach, this study analyzes various scientific publications, regulations, and relevant official documents. The research findings indicate that BAZNAS and LAZ play a significant role in optimizing the use of zakat, infaq, and sadaqah funds to support environmental programs, including renewable energy, waste management, and ecology-based economic empowerment. However, efforts to integrate zakat with green banking practices are still limited by regulatory aspects, institutional capacity, and the level of public literacy. Based on these results, this research emphasizes the importance of strengthening the regulatory framework and increasing institutional capacity in order to maximize the contribution of zakat institutions to green financing.